River Basin Management Under a Changing Climate - Ray, Ram L.; Panagoulia, Dionysia G.; Shantha Abeysingha, Nimal (IntechOpen, 2023)
River Basin Management - Under a Changing Climate is a collection of relevant research, experiments, and case study chapters. This book offers a comprehensive overview of recent developments in water resources planning, monitoring, and management using in situ measurements, modeling, and community participation. The book includes five sections and fourteen chapters that discuss water resources management, focusing on river basins, which includes quantifying water resources, evaluating water quality, and evaluating the impact of hydraulic structures on water resources management. Chapters also discuss the critical role of community/stakeholders in water resources, planning, monitoring, conservation, and management at smaller to larger river basins.